A rare case of delayed presentation of congenital diaphragmatic hernia with gastric volvulus - Tak, Bajrang; Kumar, Lalit; Singh, Jaspreet; Anuragi, Gajendra (International Journal of Research in Medical Sciences, 2016)
A Bochdalek hernia is a posterior congenital defect of the diaphragm, usually on the left hemidiaphragm, caused by a lack of closure of the pleuroperitoneal canal between the eighth and tenth week of fetal life during the embryonic development. It typically presents in the neonatal period with severe respiratory failure. Here we present a 28 year old man with history of episodes of severe dyspnea, pain in epigastric region who arrived to the emergency room, having tachypnoea with oxygen saturation 80% on room air. During his medical work-up we incidentally found gastric volvulus with diaphragmatic hernia. It was managed with reduction of the herniated and rotated stomach and spleen back to the peritoneal cavity and closed the defect by open approach. This type of hernia is uncommon in adults. In this age group, there are two different clinical presentations: asymptomatic patients who are diagnosed incidentally when abdominal organs are found in the thorax in a chest X-ray, and symptomatic patients due to side effects of incarceration, strangulation, hemorrhage and visceral perforation in the chest cavity.